Condiçőes de cristalização dos charnockitos ígneos no nordeste do brasil (2000)
Las rocas máficas y félsicas con ortopiroxeno (hiperstena) son los componentes importantes de la zona de transición que separa el Cratón Arqueano de San Francisco y el Cinturón Móvil Costero Neoproterozóico, en el extremo sur del estado de Bahía, Brasil.  Las charnockitas presentan texturas relictas magmátlcas. Los cálculos termobarométricos hacen pensar en temperaturas entre 700 - 800oC y presiones de 4,5 a 5,5 kbar (12 a 17 km de profundidad) para la generación de estas rocas. Evidencias de campo, complementadas por datos mineralógicos y texturales, hacen pensar en un origen asociado a la fusión parcial de corteza continental en las condiciones de la facies granulita / Abstract.  Orthopyroxene-bearing felsic and mafic rocks are important components of the transition zone between the Archean São Francisco Craton and the late proterozoic Coastal Mobile Belt in southeastern Bahia, Brazil. The charnockites have relict magmatic textures. Thermobarometic calculations based on several Exchange thermometers and one barometer suggest temperatures between 700 and 800oC and a pressure of 4,5 and 5,5 kbar (-12-17 km depth) for the generation of these rocks.  In the studied rocks there are many textural indications for the instability of minerals used in the exchange thermobarometers, suggesting that the interpretation of temperature and pressure conditions of granulite facies rocks is more accurate when based on the principles of the equilibrium of phases.  Field evidence, supplemented by mineralogical and textural data suggests an origin by partial melting of deep continental crust under the dry conditions of granulite facies.